An enantiopure N,N,O heteroscorpionate ligand derived from (-)-menthone - Bleifuß, Sascha; Hofmann, Fabian; Burzlaff, Nicolai (Zeitschrift für Anorganische und Allgemeine Chemie, 2013)
A new enantiopure heteroscorpionate ligand HOPhbpm (2) was synthesized in a one-pot synthesis. Ligand 2 was obtained in a pyridine-catalysed Peterson rearrangement starting from menthopyrazole, thionyl chloride, and salicylaldehyde. The evidence of κ-coordination of the ligand was shown by the formation of a tetrahedral zinc complex [Zn-κ-(OPhbpm)CH] (3) as well as an molybdenum complex [Mo-κ-(OPhbpm)O Cl] (4). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Bis(pyrazol-1-yl)acetic acid bearing ferrocenyl substituents - Tampier, Stefan; Bleifuß, Sascha; Abd-Elzaher, Mokhles M.; Sutter, Jörg; Heinemann, Frank Wilhelm; Burzlaff, Nicolai (Organometallics, 2013)
The new compound 4-ferrocenyl-3,5-dimethylpyrazole (4; fcdmpzH) has been synthesized from 4-iodo-3,5-dimethyl-1-tritylpyrazole (2) via a Negishi type cross-coupling reaction and subsequent deprotection of the intermediate 4-ferrocenyl-3,5-dimethyl-1-tritylpyrazole (3; fcdmpzTrt). Reaction of the pyrazole 4 with dichloromethane, base, and phase transfer catalyst results in the chelating N,N ligand bis(4-ferrocenyl-3,5-dimethylpyrazol-1-yl)methane (5; bfcdmpzm). Bis(4-ferrocenyl-3,5-dimethylpyrazol-1-yl)ketone (6; bfcdmpzk) is obtained by reacting 4 with NEt and triphosgene. The N,N,O heteroscorpionate ligand bis(4-ferrocenyl-3,5-dimethylpyrazol-1-yl)acetic acid (7; H[bfcdmpza]) can be accessed by reacting pyrazole 4 with dibromoacetic acid, KOtBu, and phase transfer catalyst and subsequent acidic workup. The heteroscorpionate ligand H[bfcdmpza] (7) is suitable to bind metal ions in a κ coordination mode, as could be proven by the formation of a the bis-ligand complex [Fe(bfcdmpza)] (8). The molecular structures of 3, 5, 6, and 8 have been obtained by single-crystal X-ray structure determination. The electrochemical properties of the four ferrocenyl-substituted compounds 3-6 have been studied by cyclic voltammetric measurements and discussed as well. © 2013 American Chemical Society.

Cu(i) catalysed cyclopropanation with enantiopure scorpionate type ligands derived from (+)-camphor or (-)-menthone - Godau, Tom; Bleifuß, Sascha; Müller, Astrid; Roth, Thomas; Hoffmann, Susanne; Heinemann, Frank Wilhelm; Burzlaff, Nicolai (Dalton Transactions, 2011)
One-pot syntheses of three new enantiopure heteroscorpionate ligands derived from (+)-camphor or (-)-menthone are described. The ligands are obtained by reacting pyrazoles derived from (+)-camphor or (-)-menthone with sodium hydride and thionyl chloride. Subsequent reactions with pyridine and various aldehydes afford the tripod ligands in multi-gram amounts. Especially the menthopyrazole based ligand 6 showed encouraging ee values up to 69% in the Cu(i) catalysed enantioselective cyclopropanation of styrene with ethyl diazoacetate. © 2011 The Royal Society of Chemistry.